On the importance of advanced constitutive models in finite element simulations of deep tunnel advance. (October 2018) - Schreter, M.; Neuner, M.; Unteregger, D.; Hofstetter, G.
Abstract: In a numerical study of deep tunneling, considering a stretch of the Brenner Base Tunnel, the influence of the employed constitutive models for rock mass and shotcrete on the predicted mechanical behavior of a tunnel structure is investigated. Departing from the standard numerical model, commonly employed in engineering practice, the complexity of both the constitutive models and the securing measures is increased gradually. The respective predicted responses of the tunnel structure are assessed and they are compared with available measurement data from the tunnel construction site. The numerical results, computed on the basis of the advanced material models, provide important insights into potential failure mechanisms of a deep tunnel structure.